Effect of intravenous iron on endogenous erythropoietin and FGF-23 secretion in patients with chronic kidney disease - Katarzyna Muras-Szwedziak; Ewa Pawłowicz-Szlarska; Michał Nowicki (Renal Failure, 2023)
Introduction It has been observed that intravenous iron administration may suppress endogenous production of erythropoietin (EPO). We postulate that this effect may be mediated by increased FGF-23 secretion.Aim of the study To evaluate the short-term effect of intravenous iron sucrose administration on endogenous EPO secretion in patients with chronic kidney disease (CKD).Materials and methods The cohort comprised 35 nondialysis patients with CKD stages 3–5. All received 100 mg of intravenous iron (III)-hydroxide sucrose complex daily for five consecutive days. Plasma EPO, iFGF-23, cFGF-23, PTH, bone alkaline phosphatase (BAP), phosphorus (PO4), calcium (Ca), and high-sensitive C-reactive protein (CRP) were measured before, and two hours after, the first and third iron infusions, and after completing iron therapy.Results EPO concentration at the end of iron treatment was significantly lower than two hours after the first iron infusion (p = 0.0003) and before the third dose (p = 0.0006) (12.6 [10.2, 41.4] mIU/mL. vs. 30.9 [15.9, 54.2] mIU/mL and 33.4 [15.4, 56.7] mIU/mL, respectively). Conversely, plasma iFGF-23 was significantly higher before the third dose (61.1 [18.6, 420.1 4] pg/mL; p = 0.025) and after the course of treatment (92.1 [28.4, 878.1] pg/mL; p = 0.004) compared to pretreatment value (48.4 [16.2, 420] pg/mL). cFGF-23 concentration was significantly lower than baseline after the first iron dose (491.8 [257.7, 1086.3] vs. 339.2 [75.4, 951.2] RU/mL; p = 0.005) and after treatment (398.7 [90.4, 1022.3] RU/mL; p = 0.025). No significant linear correlation was found between changes in plasma EPO and FGF-23.Conclusions Although intravenous iron therapy causes parallel increase of FGF-23 and supression of endogenous EPO, these two effects seem to be independent.